Congress of Neurological Surgeons Systematic Review and Evidence-Based Guidelines on the Management of Patients With Nonfunctioning Pituitary Adenomas: Executive Summary. Issue 4 (October 2016) - Aghi, Manish K.; Chen, Clark C.; Fleseriu, Maria; Newman, Steven A.; Lucas, Joshua William; Kuo, John S.; Barkhoudarian, Garni; Farrell, Christopher J.; Sheehan, Jason; Ziu, Mateo; Dunn, Ian F.
Abstract : BACKGROUND: Nonfunctioning pituitary adenomas (NFPAs) are the most frequent pituitary tumors. OBJECTIVE: To create evidence-based guidelines for the initial management of NFPAs. METHODS: A multidisciplinary task force composed of physician volunteers and evidence-based medicine-trained methodologists conducted a systematic review of the literature relevant to the management of NFPAs. To ascertain the class of evidence for the posttreatment follow-ups, the task force used the Clinical Assessment evidence-based classification. RESULTS: Seven topics of importance were chosen for detailed evaluation. The topics addressed include preoperative evaluation, primary treatment, treatment options for residual tumors after surgery, and postoperative patient management. For preoperative patient evaluation, the guideline task force focused on preoperative imaging, preoperative laboratory evaluation, and preoperative ophthalmologic evaluation. For primary treatment, this guideline addresses surgical resection, medical therapy, radiation therapy, the natural history of untreated tumors, surgical methodologies, such as endoscopy, microscopy, or craniotomy, and intraoperative adjuncts like neuronavigation, cerebrospinal fluid diversion, or intraoperative imaging. For residual tumor treatment, the guideline task force evaluated radiation vs observation. Additional topics addressed in this guideline regarding postoperative patient management include the frequency of postoperative imaging, postoperative endocrine evaluation, and postoperative ophthalmologic evaluation. CONCLUSION: Although there is clearly a need for more randomized trials generating higher levels of evidence to help guide physicians managing NFPAs, the existing evidence provided valuable data upon which the guidelines described in the 7 articles generated from this effort are based. The full guidelines document can be located athttps://www.cns.org/guidelines/guidelines-management-patients-non-functioning-pituitary-adenomas . ABBREVIATION: NFPA, nonfunctioning pituitary adenoma